Answer:
- 13
Step-by-step explanation:
f(1) = 7
f(n) = f(n − 1) – 4
f(₂) = f(1) – 4 = 7 - 4 = 3
f(₃) = f(₂) – 4 = 3 - 4 = -1
f(₄) = f(3) – 4 = (-1) - 4 = - 5
f(₅) = f(₄) – 4 = (- 5) - 4 = - 9
f(₆) = f(₅) – 4 = (- 9) - 4 = - 13
The value of f(6) is -13, calculated based on the provided recursive formula where each term is four less than the previous.
We are given that f(1) = 7, and the recursive equation for n is f(n) = f(n − 1) – 4. Since the equation shows that each next term is four less than the previous one, we can calculate the following iterations:
So, the value of f(6) is -13.
#SPJ2
a. (3)(6+10) = 18 + 30
b. 18 + 30 = 30 + 18
c. (3)(6) + (3)(10) = 3(16)
d. 48 = 48
Let the equation of a line be described by Equation A:
10y - 5x = 40
What are the y-intercept and slope of the line?
a. The y-intercept is 40, and the slope is 10
b. The y-intercept is 10, and the slope is 40
c. The y-intercept is 40, and the slope is 2
d. The y-intercept is 4, and the slope is 0.5